Fermentação alcoólica empregando leveduras floculantes em sistema de reatores torre - Marquez, Líbia Diniz Santos (2014)
Bioethanol production is an interesting alternative for the replacement of petroleum-based fuels. In order to reduce the production costs, studies have been driven toward finding alternative strains and processes that achieve high yields and productivities for alcoholic fermentation. The use of flocculant yeast is interesting because it shows facilitate separation and thus reusing cells by decantation process. In the present work the use of a flocculantSaccharomyces cerevisiae strain in continuous process was studied employing two tower reactors in series. In the experiments synthetic mediumwas used and the ethanol and sugar analyzes were done by liquid chromatography. Six flocculant yeast strains were evaluated for their fermentative capacity, which resulted in the choice of the strain C2/00, donated by CPQBA. After choosing the strain, the influence of temperature, pH and agitation rate on flocculation and fermentation yield were analyzed, and the best results were obtained at 32°C, pH 4.5 to 5.0 and 150 rpm.The sedimentation velocity of flocculant yeast was influenced by pH, obtaining the highest sedimentation specific velocity, 0.240 min-1 at pH 5.0 and at pH 4.0 was obtained 0.178 min-1. These velocities values alloweda good separation of flakes in the supernatant medium during the fermentation process, facilitating the cells recirculation. It was studied the effectiveness of using natural and commercial antibiotics to control contamination of fermentation and obtained satisfactory results with the use of the Kamoran 6ppm , Beta Bio 35 ppm and 50 ppm for nalidixic acid and ampicillin. It was analyzed several process conditions until reaching the configuration of two tower reactors connected in series with decanters for effluents of both reactors and cell recirculation to the respective reactor. This system was operated satisfactorily and the recirculation of cells ensured a better mixture in the reactor, reaching high yields and high productivities. A Central Composite Design (CCD) was applied to study the simultaneous influence of sucrose concentration in the system feed (S0), recycle flow rate for reactor first(V) and total residence time (TR). The best results were obtained at the central point (S0 = 225 g/L, V = 5 mL/s and TR = 6 h), which were yield 92.4%, productivity of 17.37 g/L.h and 16.03 g/L residual sugar. After studies using synthetic medium, experiments wererealizedwith sugar cane juice as sugar sourcein the reactor system under study and it was obtained a yield of 93.8%.